The school from the perspective of adolescents of the Generation Z - Ana Flávia Campeiz; Wanderlei Abadio de Oliveira; Luciana Mara Monti Fonseca; Luciane Sá de Andrade; Marta Angélica Iossi Silva (Universidade Federal de Goias, 2017)
The objective was to analyze the school meaning for students part of the Generation Z from a High School of a capital city in the north region of Brazil. We conducted a qualitative study with 57 participating adolescents. We collected data through focus groups, and we analyzed it using content analysis, thematic modality. The results showed two thematic nuclei: School, a space to learn and to prepare for the future; and, Standoff and in steps, the school that needs to re-discover itself. Adolescents comprehend the school as a space to build learning, but they consider the virtual environment also as a space to build knowledge. This study offers contributions to rethink the education directed to the digital generation, as an effort to incorporate new languages and innovations to teaching, besides guiding the definition of plans and routes of care and, health attention that considers the new relationships between adolescents and technology.